Developing Computerized Monitoring and Evaluation Systems for Small Agricultural Development Projects : lessons from the Eastern Caribbean - Mendelssohn, Gaie. (Brighton, England : Institute of Development Studies, 1991)
This paper seeks to address difficulties that emanate from development agency responsible to implementing small projects phases in establishing a capacity for monitoring an ongoing evaluation with minimal resources.
Cover title.
"August 1991."
Includes bibliographical references (p. 47-50).
rua 12/06/17
Loans
Keywords: Agricultural development projects; Agriculture; Agricultural development projects - data processing; Caribbean Area